(untitled) (Damascus University Journal of Historical Studies, 2026)
The article includes information about the emergence of the science of history among Arab Muslims, and the stages of development of historical documentation from the era preceding the advent of Islam, known technically as the pre-Islamic era, through the Rashidun and Umayyad eras, then the Abbasid era in its various stages until the first Mamluk era 648-784 AH / 1250-1382 AD, and information about the emergence of the sciences of the Noble Prophetic Hadith and the stages of its development during the successive Islamic eras as well, and then it explains the nature of the relationship between these two sciences, and the mutual influences of each on the other science, and sheds light on the most prominent of those who combined these two sciences in the first Mamluk era.